Falsely Negative 99mTc-Antigranulocyte Immunoscintigraphy and Positive 99mTc-HMPAO-La be I led Leukocyte Scan in Active Crohn’s Disease - Ivančević, V.; Schwörer, H.; Sandrock, D.; Kaufmann, Cornelia; Ramadori, G.; Emrich, D.; Munz, D. L. (Nuklearmedizin - NuclearMedicine, 1995)
A 19-year-old woman with active Crohn’s disease under immunosuppressive therapy underwent scintigraphy with 99mTc-anti-NCA-95 antigranulocyte antibodies in order to determine the extent of inflammation. It turned out to be falsely negative whereas a 99mTc-HMPAO-labelled leukocyte scan revealed a marked terminal ileitis and pancolitis. It is assumed that immunosuppressive therapy was the main reason for the falsely negative antibody scan, possibly affecting the red bone marrow where most of the antibodies bind to granulocytes. Peripheral leukocytes labelled in vitro do not seem to be subject to these hypothetical effects on red bone marrow.
Keywords: Antigranulocyte immunoscintigraphy; labelled leukocytes; Crohn’s disease; immunosuppression